Respuesta :
Answer:
I assume you are looking for the x and y values of the two equations? if not message me!
y=–2
x=1
Step-by-step explanation:
Multiply the first/top tearm by –3 so we can "get rid of" the X's with the addition of both equations. we are then left with: 14y=-28
We can now divide both sides by 14 to get y by itself so we are left with: y=–2
plugging our y value back into the first equation we get: 3x+8=11. we subtract 8 from both side and are left with: 3x=3. dividing both side by 3 we can get x by itself and are left with: x=1
To check, we plug x and y both into the first equation we get: 3+8=11 (which it does). Or we can plug both of them into the second equation and we get:9-4=5 (which it does)
Answer:
Below in bold.
Step-by-step explanation:
3x-4y=11
9x+2y=5
Multiply the first equation by 3:
9x - 12y = 33
Subtract the above from the second equation:
2y - (-12y) = 5 - 33
14y = -28
y = -2.
Now plug y = -2into the first equation:
3x - 4(-2) = 11
3x = 11 - 8 = 3
x= 1.